Hydraulic composition
By adding crystalline layered sodium silicate to hydraulic compositions, the initial strength is enhanced, addressing the reduction in strength observed when blast furnace slag is partially replaced with cement, while maintaining fluidity.
Patent Information
- Application Number
- JP2023187859
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-11-01
- Publication Date
- 2025-05-15
AI Technical Summary
The replacement of blast furnace slag with a part of the cement in hydraulic compositions results in a reduction of initial strength, as observed in existing technologies.
Incorporating crystalline layered sodium silicate into the hydraulic composition, which enhances the latent hydraulic properties of blast furnace slag, thereby improving the initial strength without compromising fluidity.
The use of crystalline layered sodium silicate in the hydraulic composition significantly increases the initial strength (compressive strength at one day of age) while maintaining or improving fluidity, even when blast furnace slag is partially replaced with cement.
Smart Images

Figure 2025076117000001 
Figure 2025076117000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydraulic composition containing Portland cement, blast furnace slag, crystalline layered sodium silicate, fine aggregate and water. More specifically, the present invention relates to a hydraulic composition containing blast furnace slag that improves early strength development. More specifically, the present invention relates to a hydraulic composition containing blast furnace slag that improves early strength development by utilizing crystalline layered sodium silicate in the hydraulic composition containing blast furnace slag. [Background technology]
[0002] In relation to recent global environmental problems, the effective use of waste, by-products, etc. has become an important issue. Taking advantage of the characteristics of the cement industry and cement manufacturing facilities, the effective use or treatment of waste as raw materials or fuel during cement manufacturing is considered effective from the viewpoint of safety and large-scale disposal.
[0003] The cement industry is a mass production and mass consumption industry, and it is considered important for it to effectively use or process waste materials as raw materials or fuels during cement production, and to produce cement efficiently while conserving resources and energy.
[0004] Meanwhile, from the perspective of global warming, the cement industry is positioned as an industry with high CO2 emissions. CO2 emitted in the cement industry is due to the decarbonation of limestone, which is the raw material for clinker, during the cement manufacturing stage. Blended cement with a reduced amount of clinker is considered effective for reducing CO2 emissions in the cement industry. One of the components of such blended cement is blast furnace cement, which contains blast furnace slag, and of these, blast furnace cement type B specified in JIS R 5211 (the amount of blast furnace slag in blast furnace cement is more than 30% by mass and not more than 60% by mass) is the most widely used. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Takeshi Iyoda: Concrete using large amounts of ground granulated blast furnace slag, Concrete Engineering, Vol. 52, No. 5, pp. 409-414 (2014) [Non-Patent Document 2] Atsushi Tanidagai et al.: Properties of Blast-furnace Cement Type A using clinker with adjusted mineral composition, Proceedings of the Cement and Concrete Society, Vol. 66, pp. 338-345 (2012) Summary of the Invention [Problem to be solved by the invention]
[0006] However, when blast furnace slag is used as a cement admixture to replace part of cement, there is a problem that the initial strength is lower than when cement is used alone (Non-Patent Documents 1 and 2). Therefore, the present invention provides a hydraulic composition which improves early strength development when blast furnace slag is substituted for part of cement. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems, and have found that crystalline layered sodium silicate acts as a stimulant that draws out the latent hydraulic properties of blast furnace slag.
[0008] As a result, they discovered that the Na2O contained in crystalline layered sodium silicate increases the latent hydraulic properties of blast furnace slag, and that SiO2 reacts with cement to form hydrates, thereby increasing the early strength, which led to the completion of the present invention.
[0009] Applications of hydraulic compositions include mortar, ready-mix concrete, and secondary factory products. When water glass or powdered sodium silicate (sodium silicate), which are commonly known as quick-setting agents, is added to ready-mix concrete, the alkali concentration rises rapidly, causing a quick-setting effect, which leads to a significant deterioration in workability in terms of fluidity and viscosity. However, it has been discovered that crystalline layered sodium silicate can ensure fluidity in addition to improving early strength development because the alkali concentration rises slowly when dissolved.
[0010] That is, the present invention is a hydraulic composition containing Portland cement, blast furnace slag, crystalline layered sodium silicate, fine aggregate and water, wherein the Portland cement is 40 parts by mass or more and less than 70 parts by mass, the blast furnace slag is more than 30 parts by mass and not more than 60 parts by mass (wherein the total of Portland cement and blast furnace slag is 100 parts by mass), the crystalline layered sodium silicate is more than 0 parts by mass and not more than 12 parts by mass per 100 parts by mass of Portland cement and blast furnace slag, the ratio W / B of the mass W of water to the total mass B of Portland cement and blast furnace slag is 0.25 to 0.70, and the ratio S / B of the total mass S of crystalline sodium silicate and fine aggregate to the total mass B of Portland cement and blast furnace slag is 0.3 to 4. In the above hydraulic composition, the crystalline layered sodium silicate is represented by the following formula (1): Na x H (2-x) ySi2O5 zH2O (1) (In the formula, x is a number greater than 0 and equal to or less than 2, y is a number equal to or less than 1±0.1, and z is a number greater than 0 and equal to or less than 5.) It is preferable that the composition of the compound is as follows: Effect of the Invention
[0011] According to the present invention, the hydraulic composition of the present invention can improve the early strength (compressive strength at one day of age) development without decreasing the fluidity even when blast furnace slag is substituted for part of the cement. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The hydraulic composition of the present invention is a hydraulic composition containing Portland cement, blast furnace slag, crystalline layered sodium silicate, fine aggregate and water, the Portland cement being 40 parts by mass or more and less than 70 parts by mass, the blast furnace slag being more than 30 parts by mass and not more than 60 parts by mass (wherein the total of Portland cement and blast furnace slag is 100 parts by mass), the crystalline layered sodium silicate is more than 0 parts by mass and not more than 12 parts by mass per 100 parts by mass of Portland cement and blast furnace slag, the ratio W / B of the mass W of water to the total mass B of Portland cement and blast furnace slag is 0.25 to 0.70, and the ratio S / B of the total mass S of crystalline sodium silicate and fine aggregate to the total mass B of Portland cement and blast furnace slag is 0.3 to 4. When blast furnace slag is substituted for a part of cement as described above, the initial strength is lowered compared to when cement is used alone. Therefore, in the present invention, crystalline layered sodium silicate is added to improve early strength development when blast furnace slag is substituted for part of the cement.
[0013] The Portland cement used in the present invention is a known Portland cement as specified by the JIS standard. Specifically, it is one that satisfies JIS R 5210 "Portland cement", and includes various types of Portland cement such as normal, early strength, super early strength, medium heat, low heat, and sulfate resistant.
[0014] As the blast furnace slag used in the present invention, blast furnace slag known as a cement admixture can be used. Specifically, any blast furnace slag produced as a by-product from a steelworks can be used without any restrictions as long as it is crushed. The fineness of the blast furnace slag may be within the range of general use, and is preferably 3000 to 8000 cm. 2 It is preferable that the molecular weight is adjusted to 1 / g.
[0015] In the present invention, the amount of Portland cement and blast furnace slag cement used is 40 parts by mass or more and less than 70 parts by mass, and the amount of blast furnace slag used is more than 30 parts by mass and not more than 60 parts by mass, assuming that the total amount of Portland cement and blast furnace slag is 100 parts by mass. When Portland cement contains blast furnace slag as a minor mixed component as specified in 5.3 (minor mixed components) of JIS R 5210, the amount of this blast furnace slag is included in the amount of the blast furnace slag.
[0016] Instead of using Portland cement and blast furnace slag individually, a blended cement consisting of Portland cement and blast furnace slag may be used. As the blended cement consisting of Portland cement and blast furnace slag, the well-known blast furnace cement type B specified in JIS R 5211 can be used.
[0017] In the present invention, the crystalline layered sodium silicate is contained in an amount of more than 0 and not more than 12 parts by mass per 100 parts by mass of the total of Portland cement and blast furnace slag. By adding the crystalline layered sodium silicate in the above range, the early strength when blast furnace slag is substituted for part of the cement is increased without decreasing the fluidity (improving early strength development).
[0018] When using common sodium silicate such as water glass or powdered sodium silicate, the effect of increasing the initial strength can be obtained, but since these are non-crystalline, their solubility in water is relatively high, and when used in ready-mix concrete, for example, they significantly increase the alkali concentration in the ready-mix concrete, reducing its fluidity. In addition, they react rapidly with cement to gel, which also significantly reduces the fluidity and greatly affects workability.
[0019] When the amount of crystalline layered sodium silicate added is more than 12 parts by mass, the effect of increasing the initial strength is obtained, but the amount of alkali increases, so the required fluidity is not obtained and workability deteriorates. From the viewpoint of the effect of increasing the initial strength, the amount of crystalline layered sodium silicate added is preferably 0.9 parts by mass or more, and more preferably 2 parts by mass or more, per 100 parts by mass of the total of Portland cement and blast furnace slag. When the amount of crystalline layered sodium silicate added is 2 parts by mass or more, it is possible to make the compressive strength ratio, for example, 120% or more compared to the compressive strength at 1 day of age when crystalline layered sodium silicate is not added.
[0020] The crystalline layered sodium silicate is a sodium silicate which exhibits an orthorhombic or monoclinic crystal structure and has a layered structure.
[0021] Such crystalline layered sodium silicate is specifically Na2Si 22 O 45 Kenyaite, Na2Si, represented by xH2O 14 O 29 Magadiite, represented by xH2O, Na2Si8O 17 Examples include those with the formula Na2Si2O5, etc.
[0022] Among these, the following formula (1) is preferred because the increase in alkali concentration during dissolution is gradual. Na x H (2-x) ySi2O5 zH2O (1) (In the formula, x is a number greater than 0 and equal to or less than 2, y is a number equal to or less than 1±0.1, and z is a number greater than 0 and equal to or less than 5.) The crystalline layered sodium silicate represented by the following formula is preferably used.
[0023] The crystalline layered sodium silicate represented by formula (1) may contain metal elements such as Na, K, Mg, Ca, and Al, as long as the effects of the present invention are not adversely affected. The amount of these elements mixed in is preferably 0.005 mol or less per mol of Na.
[0024] Crystalline layered sodium silicate shown in formula (1) dissolves after reacting with water and changing its crystal phase to kanemite (NaHSi2O5·3H2O). Therefore, it takes time for it to dissolve, and it is presumed that the increase in alkali concentration is gradual.
[0025] The crystalline layered sodium silicate represented by formula (1) is commercially available, and specific examples thereof include "Purifeed" (Na2Si2O5) manufactured by Tokuyama Corp. The crystalline layered sodium silicate exists in the form of powder or granules, and its particle size is 10 to 100 μm, preferably 30 to 80 μm.
[0026] The fine aggregate used in the present invention can be any known fine aggregate used in the manufacture of general mortar or concrete, such as fine aggregates such as crushed sand and pit sand, lightweight aggregates, slag aggregates as specified in JIS A 5011, size-adjusted crushed stone, seed stones used in paving materials and building materials, and other aggregates that do not affect the quality of mortar. Note that fine aggregate is aggregate that passes entirely through a 10 mm mesh sieve, 85% or more by weight passes through a 5 mm mesh sieve, and 80% or more by weight remains on a 150 μm mesh sieve. Fine aggregate can be used alone or in a mixture of two or more types.
[0027] The water used in the present invention may be any known water used in the production of general mortar or concrete, without any particular limitations. Specifically, industrial water, tap water, etc.
[0028] The hydraulic composition of the present invention is used in the form of mortar or concrete. When it is used in the form of concrete, it may be mixed with coarse aggregates that are usually used in the manufacture of concrete, such as river gravel, mountain gravel, crushed stone, etc.
[0029] In addition to the above-mentioned Portland cement, blast furnace slag, crystalline layered sodium silicate, fine aggregate, and water, polymers for admixture with cement and known admixtures generally used in the preparation of concrete, such as air-entraining water reducing agents, high-performance water reducing agents, high-performance air-entraining water reducing agents, air content regulators, and setting accelerators, may be added within a range that does not impair the effects of the present invention.
[0030] In the hydraulic composition of the present invention, the ratio W / B of the mass of water W to the total mass B of Portland cement and blast furnace slag is 0.25 or more and 0.70 or less, and the ratio S / B of the total mass S of crystalline sodium silicate and fine aggregate to the total mass B of Portland cement and blast furnace slag is 0.3 or more and 4 or less. The above ranges are both similar to the ratio W / C of the mass of water W to the mass C of cement and the ratio S / C of the mass S of fine aggregate to the mass C of cement used in general mortar.
[0031] The hydraulic composition of the present invention can be produced by mixing the components of Portland cement, blast furnace slag, crystalline layered sodium silicate, fine aggregate, and water. There is no particular restriction on the order of mixing the components. A preferred method for producing the hydraulic composition of the present invention includes a method in which Portland cement, blast furnace slag, crystalline layered sodium silicate, and fine aggregate are mixed together at the same time, and then the mixture is mixed with water. As the mixer, any mixer used for kneading paste, mortar, and ready-mixed concrete can be used without restriction, and specific examples include a pan mixer and a forced twin-shaft mixer. As described above, a mixed cement consisting of Portland cement and blast furnace slag may be used as the Portland cement and blast furnace slag. EXAMPLES
[0032] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Furthermore, not all of the combinations of features described in the examples are necessarily essential to the solution of the present invention.
[0033] (1) Combination The mix proportions are shown in Table 1. Cement, blast furnace slag, crystalline layered sodium silicate, fine aggregate and water were mixed in the proportions shown in Table 1 to prepare hydraulic compositions of the present invention. In this example, in order to evaluate the hydraulic compositions, coarse aggregate was mixed with the prepared hydraulic compositions to prepare concrete.
[0034] The water used was tap water. The cement used was ordinary Portland cement (density 3.16 g / cm) conforming to JIS R 5210 (Portland cement). 3 , powder degree 3270cm 2 The blast furnace slag used was one with a density of 2.91 g / cm3, which complies with JIS A 6206 (ground blast furnace slag for concrete). 3 , powder degree 4000cm 2 The crystalline layered sodium silicate used was a crystalline layered sodium silicate having a chemical composition represented by Na2Si2O5 (Tokuyama Corporation's "Purifeed", density 2.43 g / cm 3 , abbreviation: LS) was used. For comparison, powdered sodium silicate (density 2.50 g / cm3, abbreviation: PS) with the same SiO2 / Na2O molar ratio as the crystalline layered sodium silicate was used. Crushed sand (density 2.64 g / cm3) conforming to JIS A 5005 (crushed stone and crushed sand for concrete) was used as the fine aggregate. 3 ) and land sand (density 2.58g / cm 3 ) mixed sand was used, and the coarse aggregate was hard sandstone crushed stone (maximum size 20 mm, density 2.70 g / cm3) conforming to JIS A 5005 (crushed stone and crushed sand for concrete). 3 ) was used.
[0035] The increase in volume due to the mixing of blast furnace slag, crystalline layered sodium silicate, and powdered sodium silicate was adjusted by reducing the amount of fine aggregate.
[0036] <Reference example 1> This hydraulic composition uses only type B blast furnace cement, in which blast furnace slag is 35 parts by mass per 100 parts by mass of the total of cement and blast furnace slag, and does not contain sodium silicate.
[0037] <Examples 1 to 3> Blast furnace slag was added in an amount of 35 parts by mass per 100 parts by mass of the total of cement and blast furnace slag, and crystalline layered sodium silicate was added in an amount of 1, 3, or 10 parts by mass per 100 parts by mass of Portland cement and blast furnace slag.
[0038] <Reference example 2> This hydraulic composition uses only type B blast furnace cement, in which blast furnace slag is 45 parts by mass per 100 parts by mass of the total of cement and blast furnace slag, and does not contain sodium silicate.
[0039] <Examples 4 to 6> Blast furnace slag was added in an amount of 45 parts by mass per 100 parts by mass of the total of cement and blast furnace slag, and crystalline layered sodium silicate was added in an amount of 1, 3, or 10 parts by mass per 100 parts by mass of Portland cement and blast furnace slag.
[0040] <Reference example 3> This hydraulic composition uses only type B blast furnace cement, in which blast furnace slag is 55 parts by mass per 100 parts by mass of the total of cement and blast furnace slag, and does not contain sodium silicate.
[0041] <Examples 7 to 9, Comparative Example 1> Blast furnace slag was added in an amount of 55 parts by mass per 100 parts by mass of the total of cement and blast furnace slag, and crystalline layered sodium silicate was added in an amount of 1, 3, 10, or 20 parts by mass per 100 parts by mass of the total of Portland cement and blast furnace slag.
[0042] <Comparative Example 2> Blast furnace slag was added in an amount of 55 parts by mass per 100 parts by mass of the total of cement and blast furnace slag, and powdered sodium silicate was added in an amount of 3 parts by mass per 100 parts by mass of the total of Portland cement and blast furnace slag.
[0043] [Table 1]
[0044] *1 Water-powder ratio (%) = {water (kg) / [cement (kg) + blast furnace slag (kg)]} x 100 *2 Blast furnace slag (parts by mass) = {blast furnace slag (kg) / [cement (kg) + blast furnace slag (kg)]} x 100 *3 Sodium silicate (parts by mass) = {Sodium silicate (kg) / [Cement (kg) + [Blast furnace slag (kg)]} x 100
[0045] (2) Slump measurement The slump immediately after mixing was measured in accordance with JIS A 1101:2020 "Concrete slump test method." The standard is 18.0±1.5cm, and a large slump indicates high fluidity, while a small slump indicates reduced fluidity. This is a physical property value that serves as an indicator of workability. The results are shown in Table 2.
[0046] (3) Measurement of daily intensity The compressive strength of the concrete was measured at one day of age in accordance with JIS A 1108:2018 "Method of testing compressive strength of concrete". The size of the specimen was Φ100×200mm. The results are shown in Table 2.
[0047] [Table 2]
[0048] Examples 1 to 9 showed increased 1-day strength and a prescribed range of slump values compared to Reference Examples 1, 2, and 3. These results show that the hydraulic composition of the present invention, which contains more than 0 parts by mass and not more than 12 parts by mass of crystalline layered sodium silicate per 100 parts by mass of Portland cement and blast furnace slag in total, can achieve an effect of increasing early strength without decreasing fluidity.
[0049] In Comparative Example 1, the amount of crystalline layered sodium silicate added was large, which reduced fluidity and made mixing difficult, making it impossible to evaluate.
[0050] In Comparative Example 2, the one-day strength exceeded that of Reference Example 3, but the specified slump value was not achieved, and it is clear that when general sodium silicate (sodium silicate powder) is used instead of crystalline layered sodium silicate, the fluidity decreases and the workability deteriorates.
Claims
1. A hydraulic composition comprising Portland cement, blast furnace slag, crystalline layered sodium silicate, fine aggregate and water, wherein the Portland cement is 40 parts by mass or more and less than 70 parts by mass, the blast furnace slag is more than 30 parts by mass and 60 parts by mass or less (provided that the total of Portland cement and blast furnace slag is 100 parts by mass), the crystalline layered sodium silicate is more than 0 part by mass and 12 parts by mass or less per 100 parts by mass of Portland cement and blast furnace slag, a ratio W / B of a mass W of water to a total mass B of Portland cement and blast furnace slag is 0.25 to 0.70, and a ratio S / B of a total mass S of crystalline sodium silicate and fine aggregate to a total mass B of Portland cement and blast furnace slag is 0.3 to 4.
2. The crystalline layered sodium silicate is represented by the following formula (1): Yes x H (2-x) Yes 2 Oh 5 ・zH 2 O (1) (In the formula, x is a number greater than 0 and equal to or less than 2, y is a number equal to or less than 1±0.1, and z is a number greater than 0 and equal to or less than 5.) 2. The hydraulic composition according to claim 1, having a chemical composition represented by the formula: